Mathematical Model for BOD in Waste Water Discharges from Al Dora Refinery in Baghdad (Journal of Engineering, 2012)
This research consists of two parts, the first part concern with analyzing the collected data of BOD and COD values in discharge waste water from Al-Dora refinery during 2010 to find the relationship between these two variables The results indicates that there is a high correlation between BOD and COD when using a natural logarithm model (0.86 ln(COD)) with correlation coefficient of 0.98. This relationship is useful in predicting the BOD value using the COD value. The second part includes analyzing collected data from the same site in order to find a relationsip between BOD and other parameters COD, Phenol(phe), Temperature(T), Oil, Sulphat(SO4),pH and Total dissolved solids( TDS) discharged from the refinery. The results indicated that the best mathematical model is BOD= 0.786 (ln(COD))^2 - 3.077E83/Exp(10T) + 1.76E+48/Exp(0.1TDS)- 5.6507/Exp(100Phe) With correlation coefficient of 0.873. The presented research demonstrates many conclusions regarding the relation between BOD and other pollutions, it is clear that the relation between BOD and COD is a direct relation, while it’s a reverse relation with other pollutions and it’s also clear that a linear model can be used to represent the relation between BOD and COD for a value of COD approximately less than (50 mg/L).